The relationship between service performance and physical strength focusing on speed and spin rate in Japanese elite junior tennis players - Nahoko Koya; Tetsu Kitamura; Hiroo Takahashi (Universidad de Granada, 2021)
Service is the most powerful and potential shot in tennis. To reach global elite status, Japanese players, being generally inferior in height, must overcome the limitations in service performance. If their height is insufficient, they must improve their speed service performance while maintaining the spin rate. Therefore, in this study, we aimed to examine the relationship between service performance according to the speed and spin rates and physical factors among national-level male and female junior tennis players. Twenty-eight elite tennis players participated in this study. Service tests were completed using the TrackMan tennis radar device. A total of 12 services per player were collected. Physical strength tests were conducted according to the Japan Tennis Association methods. Based on a previous study, 16 measurement variables related to service performance were selected. Among the male players, both the 1st and 2nd services showed significant correlations of service speed with physique and physical strength. On the other hand, no correlation was observed between service spin and physique or physical strength. Among female players, there was a significant correlation between service speed and physique, but not physical strength. In contrast to male players, there were significant correlations between service spin and some parameters of physical strength. As described above, the results were different for males and females. In conclusion, male players should focus intensively on muscular strength and power during training, whereas female players should focus on acquiring the skills needed to increase the spin rate, with strength as their secondary focus. Additionally, the increased drive from the legs can be converted to increased service speed. Therefore, male and female players should be coached on service from different perspectives.